Wirtschaftlicher Betrieb von Infrastrukturprojekten. ERP-Software als integriertes Management-Tool. - Cadez, Ivan; Kupfer, Tobias (Deutscher Verkehrs-Verl., 2010)
Im Beitrag sind die vielfältigen Vorteile und Gründe für die Anwendung von Enterprise Resource Planning (ERP)-Software als Management-Tool zur wirtschaftlichen Steuerung von betrieblichen Leistungen bei Straßeninfrastrukturprojekten dargestellt.

It is recommended to apply ERP software in the case of road projects because of contractual requirements, the obligation to keep documents in connection with meeting standards of quality as per contract and to secure compensation. Furthermore, due to the integrated application of this software in other corporate divisions, e.g. accounting, procurement, storekeeping or personnel, and aided by a uniform data bank, the development of corporate- specific, wide-ranging software is being facilitated. It is explained that transparent courses of action have a positive impact on the organizational, economic and ecological targets set by the operating authorities, while also enhancing users' sense of security. ERP software can thus be regarded as an all-inclusive management tool for planning and directing corporate achievements and for optimizing courses of action in the case of private and public operators.
ERP software application for road infrastructure projects.
Keywords: Verkehr; Verkehrsinfrastruktur; EDV-Software; Management; Projektmanagement; Projektsteuerung; Straßenbau; Infrastrukturprojekt; Public-Private-Partnership; Controlling